DEVELOPMENT OF A LOCAL WISDOM-BASED ANIMATED VIDEO FOR THE ENGLISH LEARNING OF SECONDARY-LEVEL STUDENTS’ IN SABANG CITY, ACEH PROVINCE - Zuhra, Cut Mulia; Sabrina, Sabrina; Daud, Muslem (Jurnal Visipena, 2024)
The use of video as learning media in the digital age has been prevalent. A large body of literature has shown its effectiveness in the English as a Foreign Language (EFL) classrooms as it includes audio-visuals that makes the learning appealing. However, there is very limited research devoted to developing a video animation based on a local wisdom. Hence, this study aims to develop a video animation that includes local wisdom for teaching English to secondary school students. This research employed a Research and Development method which include: (1) problem analysis, (2) data collection, (3) product design, (4) validation, (5) revision, (6) product trial (7) final product revision. The data collection instruments used are validation sheets, questionnaire and observation sheet. The research subjects were 25 students at Grade VIII of SMPN 7 and SMPN 8 in Sabang City. The observation results showed a lack of multimedia used in the English learning. The validation results by media and material experts indicated that the animated video is very appropriate in terms of the design, material, and language with validation scores of 96.66%, 97.77%, and 96.36%. Meanwhile, the questionnaire results also uncovered that the animated video is favored by the students.